Model of Policy Synergy in Fire Management in the City of Bandung - Iwan Satibi; Regan Vaughan (International Journal of Science and Society, 2023)
This research is based on the phenomenon of the city of Bandung which has a large and dense population and a high level of building density, so it is at risk of various disasters. One of the disaster risks that is quite vulnerable is the occurrence of fires in slums and densely populated areas. The high potential for fires and cases of fire incidents in the city of Bandung are empirically caused by various problems, including; Firefighters are hampered on their way, lack of understanding and knowledge of the public about fire services when providing information on fires, and traffic jams that occur on the highway, as well as crowds of residents who see the fire incident, making it difficult for firefighters to put out the fire. It is hoped that these various problems can be resolved immediately through policy synergy between the Bandung City Fire and Disaster Management Service and various other relevant agencies, so that the handling of fires in the City of Bandung can be carried out more effectively and efficiently. In line with this context, this study uses a qualitative approach through descriptive methods. Meanwhile, data collection techniques were carried out using in-depth interviews, literature studies, observation and documentation. The results of the study found that in order to synergize policies in handling fires in the city of Bandung, a clear concept and parameters were needed, so that they could be used as guidelines or references for all stakeholders involved in synergizing fire management policies. The parameters in question include; there is a common perception, potential resources, communication patterns, attitudes of policy actors, and the existence of an organizational structure.